2021
DOI: 10.7717/peerj.10951
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening behaviors

Abstract: Introduction Colorectal cancer screening program compliance in Turkey is around 20–30%. Factors that may affect preventive health behavior, mainly individuals’ values, beliefs and attitudes, should be explored. A “Health Belief Model” (HBM) scale was developed in 1950 to explain the insufficient participation of some individuals in screening programs. The scale was adopted for colon cancer in 2002. The validity and reliability study of this scale for the Turkish language was conducted in 2007. In this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
3
7
1
1
Order By: Relevance
“…This finding is consistent with that of Lemeshow and Paskett (2008) who concluded that higher screening rates were observed in married participants (41.8%) compared to those not married. On the other hand, this finding is inconsistent with that of Tekiner et al, (2021) who concluded that there was a statistically difference the Perceived Barrier score the married and single participants where it was significantly higher in single subjects than in married subjects. The was a statistically significant difference in subjects' Perceived Susceptibility of contracting colorectal cancer among the marital status groups.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding is consistent with that of Lemeshow and Paskett (2008) who concluded that higher screening rates were observed in married participants (41.8%) compared to those not married. On the other hand, this finding is inconsistent with that of Tekiner et al, (2021) who concluded that there was a statistically difference the Perceived Barrier score the married and single participants where it was significantly higher in single subjects than in married subjects. The was a statistically significant difference in subjects' Perceived Susceptibility of contracting colorectal cancer among the marital status groups.…”
Section: Discussioncontrasting
confidence: 95%
“…4,6 Moreover, we have demonstrated that married females or those with higher levels of education are also associated with favorable perceptions toward preventive behaviors; an observation consistent with trends for breast and colorectal cancer screening. 36,37 While the latter is merely a function of improved knowledge, the earlier observation warrants further investigation. Interestingly, while employment status was positively associated with adopting preventive behaviors, the association lacked statistical significance.…”
Section: F I G U R Ementioning
confidence: 89%
“…Kolorektal Kanserden Korunmaya Yönelik SİM Ölçeği alt boyutlarından alınabilecek en düşük ve en yüksek puanlar dikkate alındığında; katılımcıların en düşük puan ortalamasının "sağlık motivasyonu" alt boyutuna (13,30±3,19) ait olduğu belirlenmiştir. Bu bulgu, Yılmaz, Dereli ve Yelten, 16 Çetin, 17 Tekiner, Peker ve Doğan, 18 Baysal ve Türkoğlu 19 tarafından yapılan çalışmaların bulgularıyla tutarlı, Koçak ve Tümer 20 tarafından yapılan çalışmanın bulgularıyla tutarsızdır. Çalışma bulguları arasındaki fark, bireylerin önceki deneyimlerinden kaynaklanabilir.…”
Section: Discussionunclassified